A Short Analyses of Romanian Consumers Expenditure Behaviour During The COVID-19 Period - Anne - Marie Andreea HORDĂU (Communications of International Proceedings, 2022)
The pandemic period was nevertheless one of the years when consumers behaviour was affected. We are aware of the fact that despite the period of Spanish Flu or black death, due to modern times and advanced medicine people shouldn’t have been more affected than previous times. In this paper we are doing a short analysis of Romanian consumers during the pandemic period taking in consideration their expenditure behaviour and we try to evidence if we should expect to one or more behaviour profile after this period has ended. The result of the research will be considered useful since many companies will have to rethink their commercial strategy.
Keywords: pandemic; consumers; inequalities; consumers behaviour; expenditure; retail shop; COVID-19